Controlling Asian soybean rust (Phakopsora pachyrhizi) with Bacillus spp. and coffee oil - Dorighello, Dalton Vinicio [UNESP]; Bettiol, Wagner; Maia, Nilson Borlina; Boas de Campos Leite, Regina Maria Vilas (Elsevier B.V., 2015)
Asian soybean rust is currently the main soybean disease in Brazil and its control is primarily accomplished with fungicides. This study evaluated the potential of Bacillus spp. and coffee oil, alone and combined with fungicide, to inhibit the germination of Phakopsora pachyrhizi uredospores and control the disease on detached leaves and plants in greenhouse and field conditions. The trials were carried out using the BRS 316 RR soybean cultivar. Bacillus subtilis (QST-713) and Bacillus pumilus (QST-2808) isolates, roasted and crude coffee oils used individually, as well as coffee oils combined with half dose of fungicide, inhibited uredospore germination by 100%. In tests with detached leaves, B. subtilis (isolates QST-713, AP-3, and AP-51) and B. pumilus (QST-2808) reduced disease severity by 98.6, 75.3, 61.2, and 97.7%, respectively. The reductions resulting from crude and roasted coffee oils were 80.1 and 87.7% compared to 77.5, and 84.4%, respectively, at concentrations of 2 and 1%. Under greenhouse conditions, all treatments, except B. subtilis AP-51, reduced the area under the disease progress curve (AUDPC), while under field conditions, the B. subtilis QST-713 isolate and roasted coffee oil at 1 and 2% reduced disease severity by 23, 18, and 23%, respectively. The results indicate that B. subtilis, B. pumilus, and coffee oils exhibit the potential to control Asian soybean rust disease. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Biological control; Alternative control; Natural products; Glycine max